File Encryption and Hiding Application Based on AES and Append Insertion Steganography - G. C. Prasetyadi; R. Refianti; A. B. Mutiara (Universitas Ahmad Dahlan, 2018)
Steganography is a method of hiding secret message in other innocuous looking object so that its presence is not revealed. In this paper, a message, which is a computer file of any type and size, is hidden in a selected cover or carrier, which is a computer file of certain types. The steganography method used in this paper is called append insertion steganography method. This method is chosen as an attempt to remove the limitation of message format, which appears in many popular steganography methods. To scramble the meaning of the hidden message, AES-256 (Rijndael algorithm) is used to encrypt the message with a secret passphrase. A special block of bytes is used to identify and verify the original message so it can be recovered while retaining its integrity. The C# programming language and .NET Framework are chosen to implement the algorithm into a Windows application. In this paper, one cover file contains exactly one message file. In the testing, five random files are used as secret message. Their integrity is calculated using SHA-256 before hiding and after recovery. In the testing, they all retain their integrity, proven by exact hash values. Thus, the application as the implementation of proposed algorithm is proven feasible but only for personal use as some improvements still have to be implemented.